2020
DOI: 10.1186/s13287-020-01884-4
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin mediates histone methylation that inhibits inflammation-related stemness gene expression to diminish cancer stemness via COX-independent manner

Abstract: Background: The widely recognized anti-cancer potential of aspirin has created a broad interest to explore the clinical benefits of aspirin in cancer therapy. However, the current understanding of the molecular mechanisms involved in the anti-cancer potential of aspirin remains limited. Methods: Cancer stemness assays which contained ALDH, side population, chemo-resistance, sphere formation, and tumorigenesis were performed to validate aspirin function in vitro and in vivo. Histone modification assay was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Intriguingly, as mentioned above, asprin decreases the blood levels of several metabolites when cross checked with the human metabolome database. Our results are concordant with multiple reports showing that aspirin can suppress chemoresistance in various malignancies (27)(28)(29)(30)(31)(32). A clinical trial is currently evaluating the efficacy of aspirin and tamoxifen in combination with doxorubicin as part of standard AC-T chemotherapy for treatment of high risk ER+ or ER-breast cancer (NCT04038489 clinicaltrials.gov).…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, as mentioned above, asprin decreases the blood levels of several metabolites when cross checked with the human metabolome database. Our results are concordant with multiple reports showing that aspirin can suppress chemoresistance in various malignancies (27)(28)(29)(30)(31)(32). A clinical trial is currently evaluating the efficacy of aspirin and tamoxifen in combination with doxorubicin as part of standard AC-T chemotherapy for treatment of high risk ER+ or ER-breast cancer (NCT04038489 clinicaltrials.gov).…”
Section: Discussionsupporting
confidence: 91%
“…A value of P < 0.05 was used as the criterion for statistical signi cance. *Indicates signi cant difference with P < 0.05, **indicates signi cant difference with P < 0.01, ***indicates signi cant difference with P < 0.001 [32,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, cell-based analyses also showed that increasing doses of aspirin reduced the cancer cell viability along with long-term clonogenesis while affecting caspase-3 activity minimally (Der et al 2020 ). Besides, Zhang et al ( 2020a , b ) showed that aspirin reduced the protein levels of programmed cell death-ligand 1 (PD-L1) which is expressed in tumor cells and displays an inhibitory role in antitumor immunity in A549 and H1299 human lung cancer cell lines. Further, the promoter of PD-L1 was cloned in a luciferase reporter pGL3-basic plasmid and aspirin was shown to reduce luciferase activity of pGL3-PD-L1.…”
Section: The Origin and Development Of Nsaids: A Journey To The Pastmentioning
confidence: 99%
“…(Zhang et al 2020b ). In the study of Zhang et al ( 2020a , b ), changes in ALDH + subpopulation were investigated by using ALDH staining in A549 lung, MDA-MB231 breast, and HepG2 hepatocellular cancer cell lines. Aspirin reduced the ALDH + subpopulation along with an increase in apoptosis and a decrease in sphere formation.…”
Section: The Origin and Development Of Nsaids: A Journey To The Pastmentioning
confidence: 99%
See 1 more Smart Citation